Determinan yang Mempengaruhi Pembelian Online di Kalangan Mahasiswa - Rachmad Sholeh; Zenita Afifah Fitriani; Sugeng Eko Yuli Waluyo; Mohamad Johan Effendi; Elly Joenarni; Adil Abdillah (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
This study takes the topic effect of commitment, empathy, and trust on online purchasing decisions in the study of Mayjend Sungkono University Mojokerto Students. The sample in this study was 170 people. The research sample method is non-probability sampling with purposive sampling. Data were collected using the questionnaire method, namely by providing a list of questions or questionnaires directly to the respondents. Based on the results of multiple regression analysis, it can be concluded that all variables of commitment to empathy and trust together have a positive and significant influence on purchasing decisions on online products among Mayjend Sungkono University Mojokerto students. Keywords: Commitment, Empathy, and Trust on Online Purchasing Decisions